BEBERAPA MACAM PERLAKUAN TERHADAP PENYADAPAN AGATHIS SPP. UNTUK MENINGKATKAN BASIL GETAH - Dulsalam Dulsalam; Ishak Surnantri (Jurnal Penelitian Hasil Hutan, 1985)
An  investigation into tapping of Agathis  spp.  using several methods has been carried out in Malang Forest District,  Unit II Perum Perhutani, East  Java,  in 1983.  The  methods are designed  to  increase resin yield per  unit time by manipulating tapping time, duration and covers and orientation.The investigation reveals that:1. Average resin production of the Agathis  spp. for  one week to two weeks times using of black and white plastic covers are respectively 9,85  gram/tree and 9,61 gram/tree. Without plastic cover the yield is 7, 76 gram/tree, shightly lower then when they are covered.2. The application of black plastic cover at tapping his significantly  increased the yield up to 26,9%  and those covered with white plastic of 23,8"7o.   In both cases the resin yield is significantly higher compared to result obtained  when tapping was carried out without cover.3. Average resin yield at tapping face  oriented to in east and west from  one to two  weeks  are 7,48  gram/tree and 11,26  gram/tree, respectively.4. The tapping face oriented to the west increases the resin yield up to 50,5%  compared with that oriented to the east.5. The average resin yield for  one and two  week are respectively 8,57  gram/tree and 9,95  gram/tree.  Duration of  tapping of  the Agathis  spp. for one and two week does not effect the production level.  Therefore 2 week tappin~ is not recomended.